Echinacoside selectively rescues complex I inhibition-induced mitochondrial respiratory impairment via enhancing complex II activity. (May 2019) - Ma, Huihan; Liu, Yang; Tang, Lin; Ding, Hao; Bao, Xuxia; Song, Fang; Zhu, Min; Li, Wenwei
Abstract: Previous investigations have implicated mitochondrial dysfunction characterized by Complex I deficiency in the death of dopaminergic neurons in Parkinson's disease (PD). To date, there are no efficient therapeutic approaches to rescue mitochondrial respiratory impairment or prevent neurodegeneration in PD. The beneficial effects of echinacoside (ECH) on neurodegeneration have been reported in both in vivo and in vitro studies, yet the mechanisms underlying remain elusive and little has been investigated concerning the influences of ECH on mitochondrial respiratory impairment. Here, we compared the protection of ECH on cell injury and mitochondrial dysfunction induced by various inhibitors of Complex I-IV using human neuroblastoma SH-SY5Y cell line. We found that ECH selectively attenuates cell injury, reverses mitochondrial depolarization and bioenergetic failure caused by Complex I inhibitors, whereas it has little protection against Complex II-IV inhibitors. Further investigation demonstrated that ECH enhances Complex II activity and mitochondrial respiration in the cells treated with Complex I inhibitors. This suggests that ECH selectively rescues Complex I inhibition-induced mitochondrial respiratory impairment though elevating Complex II activity, and further confirms that ECH might have a promising potential in PD treatment. Highlights: ECH selectively rescues cell injury caused by Complex I inhibitors. ECH rescues mitochondrial respiratory impairment induced by Complex I inhibitors. ECH elevates Complex II activity in the presence of Complex I inhibitors. ECH increases Complex II expression in the presence of Complex I inhibitors.